Plant to animal protein ratio in the diet: nutrient adequacy, long-term health and environmental pressure - Fouillet, Hélène; Dussiot, Alison; Perraud, Elie; Wang, Juhui; Huneau, Jean-François; Kesse-Guyot, Emmanuelle; Mariotti, François (Frontiers in Nutrition, 2023)
Background Animal and plant protein sources have contrasting relationships with nutrient adequacy and long-term health, and their adequate ratio is highly debated. Objective We aimed to explore how the percentage of plant protein in the diet (%PP) relates to nutrient adequacy and long-term health but also to environmental pressures, to determine the adequate and potentially optimal %PP values. Methods Observed diets were extracted from the dietary intakes of French adults (INCA3, n = 1,125). Using reference values for nutrients and disease burden risks for foods, we modeled diets with graded %PP values that simultaneously ensure nutrient adequacy, minimize long-term health risks and preserve at best dietary habits. This multi-criteria diet optimization was conducted in a hierarchical manner, giving priority to long-term health over diet proximity, under the constraints of ensuring nutrient adequacy and food cultural acceptability. We explored the tensions between objectives and identified the most critical nutrients and influential constraints by sensitivity analysis. Finally, environmental pressures related to the modeled diets were estimated using the AGRIBALYSE database. Results We find that nutrient-adequate diets must fall within the ~15–80% %PP range, a slightly wider range being nevertheless identifiable by waiving the food acceptability constraints. Fully healthy diets, also achieving the minimum-risk exposure levels for both unhealthy and healthy foods, must fall within the 25–70% %PP range. All of these healthy diets were very distant from current typical diet. Those with higher %PP had lower environmental impacts, notably on climate change and land use, while being as far from current diet. Conclusion There is no single optimal %PP value when considering only nutrition and health, but high %PP diets are more sustainable. For %PP > 80%, nutrient fortification/supplementation and/or new foods are required.